THE DEVELOPMENT OF FLEXI BAR TRAINING MODEL FOR OVERWEIGHT ADULT - Yanyong Phanpheng; Ashira Hiruntrakul (Sport Scientific And Practical Aspects, 2025)
The aimed of study to develop a flexi bar training model for overweight adults. The 17 exercise experts who were exercise trainers, sport scientists, and university lecture. Delphi technique was applied for conducting the research. After 3 rounds, the researcher analyzed the data using Median, Mode and Interquartile range. The results revealed that the experts had corresponding opinion toward the development of flexi bar training model at the most important level. This research also pointed out that the experts correspondingly agreed that the components of flexi-bar exercise model and flexi bar training model were appropriate for exercise, and it was an alternative for exercise to stimulate energy expenditure rate which results in good physical fitness and biochemistry in bloods. In addition, it strengthens muscles and structures of joints of overweight adults; and it was a model for exercise program for those who have few physical activities and abnormality in physical movement in the future.